PESANTREN AMTSILATI SEBAGAI ROLE MODEL PENDIDIKAN BERBASIS ANTI RADIKALISME DI JEPARA - Nor Laila, Azzah; Rohman, Fathur (Universitas Islam Sultan Agung, 2018)
The growth of radical religious and political thought developed in Indonesia and become a serious threat to the nation. It is marked by still a lot of data of radical action and terror in Indonesia. Treatment and prevention of the spread of radical requires active participation of all parties. In that case, the role of educational institutions is very significant to help stop the rate of radicalism. Therefore, this research is trying to find the design of Islamic education based on anti radicalism, as well as portrait of Islamic educational institutions that implement antiradicalism based education system. This research is included in this type of qualitative research. While in terms of methods, this study includes case studies. The case is the subject of study in this research is the implementation of Islamic education in boarding Amtsilati anti radicalism Bangsri Jepara. Educational anti radicalism is implemented with two models, namely classical and non classical. As a boarding school with salaf and modern system, PP. Darul Falah was quite serious in printing his santri into moderate Muslims. This is evidenced by the existence of learning that is focused on anti-radicalism materials that must be followed by santri.Keywords: education, anti radicalism, Amtsilati Boarding School.